Implementasi Tools Penetration Testing Untuk Menguji Tingkat Keamanan Wi-Fi Pada Direktorat Inovasi dan Inkubator Bisnis - Tamsir Ariyadi; M. Rizky Pohan (Postgraduate, University of Mataram, 2023)
Wi-Fi networks have become a critical infrastructure in many organisations, including the Directorate of Innovation and Business Incubator. However, potential vulnerabilities in Wi-Fi networks also increase as technology advances. Therefore, testing is needed to identify and address security that can harm network users. This research aims to implement penetration testing tools in testing the security level of Wi-Fi networks at the Directorate of Innovation and Business Incubator. The penetration testing method is used to test security and assess the level of resistance to attacks on Wi-Fi in the form of simulated attacks. One of the operating systems that provides penetration testing tools that meet the needs of testing is linux times. The tools used in the penetration testing process are airmon-ng, airodump-ng, aireplay-ng, aircrack-ng, macchanger, ettercap and wireshark. The results showed that the Wi-Fi security of the Directorate of Innovation and Business Incubator still needs to be improved where the results of the four types of attacks only one failed, namely MAC Spoofing. In addition, the tests on Denial of Service, Cracking the Encryption, and Man-in-the-Middle attacks were successful. The application of anticipation by increasing Wi-Fi security based on the attacks that have been carried out can prevent these attacks.